Perancangan Chatbot Whatsapp Natural Language Processing Untuk Pelayanan Digital Universitas Nusa Putra - Fergina, Anggun; Alpariji, Salman; Sujjada, Alun (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Universitas Nusa Putra is committed to providing the best services to students and prospective students through the implementation of technology. This study uses a qualitative method with a case study on the digital services of the university's communication and marketing department, which designed a chatbot based on Natural Language Processing (NLP) on the WhatsApp platform. Using PHP and Python, this chatbot provides information about new student admissions as well as academic and non-academic information in Indonesian and English. Functionality testing using black-box testing and questionnaires showed that the chatbot has an accuracy rate of 90% and a user satisfaction rate of 87.9%. These results indicate a positive reception towards the chatbot technology at Universitas Nusa Putra. Further development may include integration with social media platforms and the university's website, as well as enhancements in security and privacy.